Housing preference for modern urban designers using fuzzy-AHP - Wang, Chen; Wood, Lincoln Christopher; Liang, Huijun (Open House International Association, 2018)
Various demands and requirements of foreign home-buyers from different background are yet unclear to most of the residential developers. The aim of this study is to blueprint a fuzzy mapping of psychological phenomena reflected in consumer behavior, and to develop a Fuzzy Analytic Hierarchy Process (Fuzzy-AHP) decision making model to assist residential developers in dealing with potential foreign customers. Through a questionnaire survey in the form of pair wise comparison matrix among 126 expatriates, this study introduces a new approach to assist residential developers dealing with expatriates' preference on house purchase in Malaysia in a simple and efficient way. With this fuzzy mapping, residential developers could utilize psychological phenomena to manipulate expatriates' preference on housing purchase rather than to merely comply passively.